2021
DOI: 10.1111/bjh.17648
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis, risk factors and therapeutic options for autoimmune haemolytic anaemia in the post‐transplant setting

Abstract: Summary Autoimmune haemolytic anaemia (AIHA) is a rare complication of allogeneic haematopoietic stem cell transplantation (HSCT), observed with an incidence of 1–5%. Paediatric age, diagnosis of non‐malignant disease, lympho‐depleting agents in the conditioning regimen, use of unrelated donor, graft versus host disease and infections have been associated with a higher risk of AIHA post HSCT. Post‐HSCT AIHA is associated with high mortality and morbidity, and it is often very difficult to treat. Steroids and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Autoimmune haemolytic anaemia (AIHA) is a condition in which an autoimmune response is mounted against the patient's own red cell antigens, leading to haemolysis [ 1 ]. Recently, AIHA has emerged as a relatively common complication of haematopoietic stem cell transplant (HSCT), with an incidence of approximately 1%–6% depending on the associated population [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Autoimmune haemolytic anaemia (AIHA) is a condition in which an autoimmune response is mounted against the patient's own red cell antigens, leading to haemolysis [ 1 ]. Recently, AIHA has emerged as a relatively common complication of haematopoietic stem cell transplant (HSCT), with an incidence of approximately 1%–6% depending on the associated population [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune haemolytic anaemia (AIHA) is a condition in which an autoimmune response is mounted against the patient's own red cell antigens, leading to haemolysis [ 1 ]. Recently, AIHA has emerged as a relatively common complication of haematopoietic stem cell transplant (HSCT), with an incidence of approximately 1%–6% depending on the associated population [ 1 , 2 , 3 ]. Previous studies have found that this complication is especially prevalent in paediatric populations, and there is limited evidence that it may be impacted by donor and recipient factors such as human leucocyte antigen (HLA) matching and donor source [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations